The gender and generational consequences of the demographic transition and population policy: An assessment of the micro and macro linkages - T. Paul Schultz (Yale University, Economic Growth Center, 2009)
The demographic transition changes the age composition of a population, affecting resource allocations at the household and aggregate level. If age profiles of income, consumption, savings and investments were stable and estimable for the entire population, they might suggest how the demographic transition would affect inputs to growth. However, existing macro and micro simulations are estimated from unrepresentative samples of wage earners that do not distinguish sex, schooling, etc. The demographic dividend” is better evaluated through case studies of household surveys and long-run social experiments. Matlab, Bangladesh, extended a family planning and maternal and child health program to half the villages in its district in 1977, and recorded fertility in the program villages was 16 percent lower than in control villages for the following two decades until 1996. Households in program villages realized health and productivity gains that were concentrated among women, while child survival and schooling increased, and household physical assets were 25 percent greater per adult than in control villages.
Keywords: J13; J21; J68; O15; 330; fertility decline; demographic transition; intergenerational transfers; gender; Demographischer Übergang; Altersstruktur der Bevölkerung; Geschlecht; Generationenbeziehungen; Schätzung; Matlab; Bangladesch